PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA BERBASIS PENDIDIKAN MATEMATIKA REALISTIK DENGAN STRATEGI HIPNOSIS MATERI HIMPUNAN KELAS VII - Muhammad Ilyas Yusuf (LPPM Universitas Pekalongan, 2011)
Based on the fore research the RME approaches were one of the teaching approaches that could improve the students’ activeness, besides the theoretic approach showed that hypnosis was one of the ways to maximize the students’ brain works, so that RME by using Hypnosis was used by the researcher to solve this problem. This study is proposed to create some Mathematics teaching instruments based on valid RME, practice and effective. The teaching instruments developed are Syllabi, Lesson Plan, and students’ activities worksheets, teaching CD, Learning Test. The method used in this research is 4- D by Thiagarajan that has been modified into 3-D such as; (1) define, (2) design and (3) develop. The results of this research are; (1) the valuators said that the Mathematics teaching Instruments based on RME was valid; (2) the researchers said that the RME using Hypnosis strategy was good (in score average 58), the researchers’ responses to the instruments were positive (in score average 82%); and (3) the students’ proportion that achieved the standardized passing grade in each cycle was 80%; the last is the average score in their prestige and activeness in the first cycle was 38,7 and 58,5; in the second cycle 77,9 and 66,4; in the third cycle 79,7 and 68,1. The summary of this research was that the Mathematics teaching instrument based on RME on the sets concept was valid, practice and effective. The researcher suggests to the SMP teachers to apply the mathematics teaching based on RME using Hypnosis Strategy on the other mathematics concepts. Key words: Realistic Mathematic Education (RME), Hypnosis.